Chanel or Channel: the motivations behind the purchase of counterfeit luxury fashion goods and the post-purchase satisfaction with the same - Delgado, Cláudia Pereira (2017)
For every kind of high value product, there will always be counterfeits and if even Rembrandt paintings could not escape of such action 400 hundreds years ago, high end fashion certainly cannot nowadays. There have always been counterfeits in fashion, however, due to the technological evolution and the actual fast pace of fashion, counterfeits are more rife than ever before. Reproducing a genuine fashion product has a great impact for luxury fashion brands. Such impact is not only regarding sales but mainly because of brand equity dilution and reputation. Therefore, there is a serious concern about fighting counterfeiting -there are laws against it and brands have already developed mechanisms to find falsifications of their own goods. However, as long as there is demand, there will be counterfeits and, consequently, it is crucial to understand the motivations behind such purchases to decrease the mentioned demand. Hence, the aim of the present thesis is to understand the motivations behind the purchase of luxury fashion counterfeits and the post-consumption satisfaction with the same. To accomplish such goal, an exploratory qualitative research was applied where consumers, fashion designers and marketing professionals were interviewed to gain new insights regarding the mentioned topic as well as how it differs from the purchase the original good. The achieved results demonstrated that the purchase of counterfeits is both due to extrinsic and intrinsic motivations. Although, the extrinsic motivations are very similar to the ones behind the purchase of the original product, intrinsic motivations differ mainly due to hedonic reasons. The expectations regarding counterfeits are usually low which make them easier to exceed comparing to originals’ expectations.